SMALL DEEP MAGNETOMETRIC ON FIELD INVESTIGATION OF GEOLOGICAL STRUCTURE OF PRECAMBRIAN BASEMENT - Reshetnyk, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this work the need for complex detailed magnetic survey work for part of the Precambrian basement outcrops. It is proposed to apply the new methodology – Small deep magnetometric, the essence of which is combined detail, complexity and innovation research. To study the outcrops of Precambrian magnetic scanning method developed for the analysis of the data suggested a comparative magnetic analysis. Their implementation demonstrated by outcrops along r. Southern Bug Haivoron region (Ukraine) allowed to amend and clarify the geological map of the Precambrian basement.